Optimization of Multi-Loop PI Control for a 6-DOF Robotic Arm Using Looptune in MATLAB/Simulink - Yuli Mauliza; Ghiyalti Novilia; M. Basyir; Muhammad Isra (Malikussaleh Journal of Mechanical Science and Technology, 2025)
This study discusses the tuning of a multi-loop control system based on Proportional–Integral (PI) controllers for a six-degree-of-freedom (6-DOF) robotic arm. Each joint is controlled individually but operates in coordination to achieve precise motion. A simultaneous tuning method using the looptune function and the slTuner interface in MATLAB is employed to optimize all six loops simultaneously, considering response time, MIMO stability, and minimal cross-coupling. Simulation results in the Simulink–Simscape model show that this method produces faster, more stable responses with reduced overshoot compared to conventional tuning. The implementation of a 2-DOF controller also eliminates overshoot and improves the performance of the Bicep joint, resulting in smoother and more accurate trajectory tracking.